2022
DOI: 10.1093/nar/gkac1158
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic phase separation of the androgen receptor and its coactivators key to regulate gene expression

Abstract: Numerous cancers, including prostate cancer (PCa), are addicted to transcription programs driven by specific genomic regions known as super-enhancers (SEs). The robust transcription of genes at such SEs is enabled by the formation of phase-separated condensates by transcription factors and coactivators with intrinsically disordered regions. The androgen receptor (AR), the main oncogenic driver in PCa, contains large disordered regions and is co-recruited with the transcriptional coactivator mediator complex su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 52 publications
1
23
0
Order By: Relevance
“…Similarly, condensates modulated by AR are described as active transcriptional regions that depend on AR's multi-domain, a marked feature of GR LLPS and other transcription factors. The splice variant AR-v7 that lacks LBD and is incapable of forming foci reveals that this domain mediates critical interaction in AR-mediated LLPS (93,106). Not surprisingly, PS with PR has also been proposed as a molecular event involved in transcriptional regulation, which was corroborated by evidence that PR dimers act as important functional units, similarly to what happens with GR (100).…”
Section: Phase Separation Associated With Other Steroid Receptors (Ar...mentioning
confidence: 93%
“…Similarly, condensates modulated by AR are described as active transcriptional regions that depend on AR's multi-domain, a marked feature of GR LLPS and other transcription factors. The splice variant AR-v7 that lacks LBD and is incapable of forming foci reveals that this domain mediates critical interaction in AR-mediated LLPS (93,106). Not surprisingly, PS with PR has also been proposed as a molecular event involved in transcriptional regulation, which was corroborated by evidence that PR dimers act as important functional units, similarly to what happens with GR (100).…”
Section: Phase Separation Associated With Other Steroid Receptors (Ar...mentioning
confidence: 93%
“…[ 16 , 25 , 77 ]. Similarly, other nuclear receptors like AR and GR also form nuclear condensates in a hormone-dependent manner [ 19 , 47 , 117 ].…”
Section: Clustered Enhancers and Tf-condensatesmentioning
confidence: 99%
“…For TBP, the disease-associated glutamine repeat expansion originated a decrease in the phase separation capacity of this TF [ 62 ]. Interestingly, it has been reported that the androgen receptor (AR), harboring a CAG repeat that when expanded causes spinal bulbar muscular atrophy (SBMA), has the ability to form phase separation condensates [ 90 ]. Curiously, the AR transcription factor interacts with MED1 by forming condensates where active transcription occurs.…”
Section: Repeat Expansions In Proteins Alter Their Condensation Behaviormentioning
confidence: 99%
“…Curiously, the AR transcription factor interacts with MED1 by forming condensates where active transcription occurs. It is reported that point mutations in several AR domains inhibit the co-condensation with MED1, altering its transcriptional activity [ 90 ]. Thus, if the CAG repeat expansion goes beyond a given threshold, as occurs in SMBA, this could impair the AR/MED1 condensate formation and, consequently, lead to transcriptional dysregulation, although no evidence for this has been reported so far.…”
Section: Repeat Expansions In Proteins Alter Their Condensation Behaviormentioning
confidence: 99%